2016
DOI: 10.1016/j.compgeo.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Thermal volume change of poorly draining soils I: Critical assessment of volume change mechanisms

Abstract: a b s t r a c tThe thermal volume change of soils is typically interpreted using the stress history and changes in yield stress with temperature (thermal softening). However, the path followed to reach a given stress state may lead to different thermal volume changes. Alternative mechanisms of thermal volume change are explored using data from the literature and isotropic, drained heating tests on compacted silt. No relationship between thermal volume change and degree of saturation was observed. However, a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 44 publications
4
25
0
Order By: Relevance
“…Inconsistent trends in thermal contraction were observed for normally consolidated specimens with decreasing degree of saturation, similar to the lack of trend with this variable observed by Uchaipichat and Khalili (2009). Coccia and McCartney (2016a) proposed that thermal volume change may instead be due to thermally-accelerated secondary creep under the previously applied mechanical stress.…”
Section: Introductionsupporting
confidence: 54%
“…Inconsistent trends in thermal contraction were observed for normally consolidated specimens with decreasing degree of saturation, similar to the lack of trend with this variable observed by Uchaipichat and Khalili (2009). Coccia and McCartney (2016a) proposed that thermal volume change may instead be due to thermally-accelerated secondary creep under the previously applied mechanical stress.…”
Section: Introductionsupporting
confidence: 54%
“…However, studies by Towhata et al [35] and Burghignoli et al [5] observed that clays with an OCR as high as 56 may either expand or contract during drained heating depending on the sequence of loading prior to the change in temperature. Coccia and McCartney [9] re-evaluated these results and found a clear relationship between the secondary compression index of soil measured prior to heating and the resulting thermal volume change. This relationship serves as the basis of a new effective-stress based constitutive model for the thermal volume change of saturated and unsaturated soils presented in this paper.…”
Section: Introductionmentioning
confidence: 90%
“…Following the re-examination of the experimental observations of Houston et al [20], Towhata et al [35], Burghignoli et al [5], as well as an independent study performed on Bonny silt by Coccia and McCartney [9] using the experimental approach described by Coccia [8] and Coccia and McCartney [10], the hypothesis of this constitutive model proposed in this study is that the thermal volume change response of saturated and unsaturated soils is due to the thermally-enhanced creep associated with the most recently applied change in effective stress. Particularly, heating of normally consolidated soils will cause an acceleration of the secondary compression process occurring prior to the start of heating, leading to contraction, while heating of overconsolidated soils will lead to either expansion or contraction depending on the direction of the most recent change in effective stress (i.e.…”
Section: Developmentmentioning
confidence: 96%
See 2 more Smart Citations